2019
DOI: 10.3389/fphys.2019.00653
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Susceptibility of Different Populations of Amblyomma sculptum to Rickettsia rickettsii

Abstract: The bacterium Rickettsia rickettsii is the etiological agent of Brazilian spotted fever (BSF), which is transmitted in Brazil mainly by the tick Amblyomma sculptum. Herein, larvae and nymphs of six populations of A. sculptum were exposed to R. rickettsii by feeding on needle-inoculated guinea pigs, and thereafter reared on uninfected guinea pigs or rabbits. Two tick populations were exposed to autochthone R.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 43 publications
2
16
0
2
Order By: Relevance
“…In addition, our tick colony of A. sculptum was also derived from this same BSF-endemic area. Indeed, this information supports strong field applicability of our results, especially because it was recently demonstrated that the susceptibility of A. sculptum to R. rickettsii varies among different tick populations, with a clear bias for higher susceptibility to an autochthone R. rickettsii strain that has already coevolved with a tick population for some time 8 .…”
Section: Infected Capybarassupporting
confidence: 85%
See 4 more Smart Citations
“…In addition, our tick colony of A. sculptum was also derived from this same BSF-endemic area. Indeed, this information supports strong field applicability of our results, especially because it was recently demonstrated that the susceptibility of A. sculptum to R. rickettsii varies among different tick populations, with a clear bias for higher susceptibility to an autochthone R. rickettsii strain that has already coevolved with a tick population for some time 8 .…”
Section: Infected Capybarassupporting
confidence: 85%
“…Regardless, it must be emphasized that techniques employing the direct detection of rickettsial DNA in bloodstream are not sensitive enough to determine bacteremic periods, especially in less severe infection courses. www.nature.com/scientificreports www.nature.com/scientificreports/ Rickettsia DNA amplification was achieved in skin samples from all capybaras during primary infection (6-26 DPI), which is similar with those results registered by Levin et al 34 in skin biopsies from R. rickettsii-infected guinea pigs (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). It is remarkable that in some capybaras (no.…”
Section: Infected Capybarassupporting
confidence: 84%
See 3 more Smart Citations